Nuff said - Tyrus, 1973- (Post Hill Press, 2023)
In this continuation of the best-selling book Just Tyrus, the author delivers a series of gut-wrenching, heart-rending and redemptive tales from his remarkable life while tackling issues of race and activism in America today and drawing parallels between current culture and his personal past.